Determinant of non-GAAP earnings management practices and its impact on firm value - Ewing Yuvisa Ibrani; Faisal Faisal; Yenny Dwi Handayani (Cogent Business & Management, 2019)
This study aims to examine the factors that explain the reasons why non-GAAP earnings management is carried out based on the fraud diamond theory (FDT). FDT is a theory widely used in behavioral research to explain the factors that cause fraud in a company. In addition, this study also explains the impact of non-GAAP earnings management practices on firm value. This study investigates 42 non-bank and financial companies listed on Indonesia Stock Exchange (IDX) for the period 2010-2017. The results of the logistic regression analysis founded that opportunity and ability were the most dominant factors causing non-GAAP earnings management. The findings of this study show that in Indonesia, there is need for greater attention from the regulators to the opportunity and capability factors to reduce the occurrence of non-GAAP earnings management.
Keywords: 650; non-GAAP earnings management; Fraud Diamond; Pressure; opportunity; rationalization; capability